Characterization of the turbot (Scophthalmus maximus) interleukin-18: Identification of splicing variants, phylogeny, synteny and expression analysis. (November 2021) - Pereiro, Patricia; Lama, Raquel; Figueras, Antonio; Novoa, Beatriz
Abstract: Interleukin-18 (IL-18) is a pro-inflammatory cytokine that belongs to the interleukin-1 (IL-1) family of cytokines. As occurs with IL-1β, it is synthetized as an inactive precursor peptide that is mainly processed by the cysteine protease caspase-1 in the inflammasome complex. In mammals, and in collaboration with IL-12, it has been described as an important cytokine controlling the Th1-mediated immune responses through the induction of IFN-γ. Although its function in mammals is well stablished, the activity of this cytokine in teleost remains to be elucidated. This could be due, among other things, to the absence of this gene in the fish model species zebrafish, but also to its complex regulation. As it was observed for rainbow trout and human, il18 splicing variants were also found in turbot, which could represent a regulatory mechanism of its bioactivity. In the case of turbot, three splicing variants were observed (SV1-3), and one of them showed an insertion of 10 amino acids in the middle of the potential caspase-1 cleavage position, reflecting that this is probably a form resistant to the processing by the inflammasome. Phylogenetic and three-dimensional analyses of turbot Il18 revealed that it is relatively well-conserved in vertebrates, although only a partial conservation of the gene synteny was observed between fish and mammals. As it was expected, turbot il18 splicing variants were mainly expressed in immune tissues under healthy conditions, and their expression was induced by a bacterial challenge, although certain inhibitions were observed after viral and parasitic infections. In the case of the viral challenge, il18 downregulations did not seem to be due to the effect of type I IFNs. Highlights: Three il18 splicing variants were identified in S. maximus (SV1-3). Turbot Il18 conserves the typical characteristics of the IL-1 family members. Turbot il18 was mainly expressed in immune tissues. Bacterial infection induced the expression of il18 . Viral and parasitic challenges inhibited il18 expression.